A Taxonomic Revision of Desmodium (Leguminosae, Papilionoideae) in Brazil - Lima, Laura Cristina Pires; Queiroz, Luciano Paganucci De; Tozzi, Ana Maria Goulart De Azevedo; Lewis, Gwilym Peter (Phytotaxa, 2014)
Desmodium is characterized mainly by lilac flowers arranged in pseudoracemose inflorescences, stamens monadelphous or diadelphous and a lomentaceous fruit generally covered by uncinate hairs. A taxonomic revision of the Brazilian species was carried out based on the analysis of 3,000 herbarium specimens, including all nomeclatural types. Field trips to the most species-rich areas of Desmodium in Brazil were undertaken, resulting in the sampling of 29 out of the 34 species recognised for  the country. We recognise 101 names as synonyms, 27 of which are new. Lectotypes were designated for 60 accepted names and synonyms, and two neotypes and one epitype were chosen. A new combination is proposed for Meibomia microcarpa, as well as a new name for Meibomia guaranitica var. microcarpa. Desmodium album is a new  record for Brazil, and D. craspediferum, D. glabrescens and D. juruenense, previously known only by type collections, were recollected during this study. All species are described, mapped and illustrated. An identification key, and comments on taxonomy and nomenclature are provided.